ROUGHNESS AND TORTUOSITY ANALYSIS OF INTERCONNECTED PORE ON POROUS MEDIA MODEL - Ridwan Sidik, Fajar
The physical properties of porous media are important things to study are the level of complexity of the pore structure connected to the porous media which affects the ease with which the fluid passes through the pore space. Complexity can be explained by the degree of roughness as well as by the characteristic hydraulic tortuosity. Determination of the level of roughness is done by formulating a mathematical definition of this characteristic. On the other hand, it is difficult to determine the tortuosity of porous media, especially hydraulic tortuosity experimentally. To study these characteristics, the Digital Rock Physics (DRP) technique approach is used. Analysis of hydraulic tortuosity on porous media can be done by utilizing digital image-based modeling followed by computational calculations through fluid flow simulation. One of the fluid flow simulation methods that can be used is the Boltzmann lattice method which is applied to the Palabos library (Parallel Lattice Boltzmann Solver). The development of the program code that utilizes the Palabos library is carried out by entering the calculation of hydraulic tortuosity based on the ratio of the average total speed (????????????????????) to the average velocity in the -x ???????? direction. Testing and data validation is carried out to ensure that the developed program code runs well and the tortuosity calculation is appropriate. The analysis was carried out by examining the relationship between diameter, roughness level, and the ratio of the model size to the canvas to the tortuosity value with the aim of analyzing the effect of the roughness parameter on the tortuosity value. From the study of several formulations of roughness level, it was found that a mathematical model based on the roll-out technique is the best approach in defining roughness. In addition, it was also found that the greater the value of the roughness parameter, the greater the error obtained in the calculation of tortuosity.